2017
DOI: 10.1038/s41598-017-15091-4
|View full text |Cite|
|
Sign up to set email alerts
|

Dogs and humans respond to emotionally competent stimuli by producing different facial actions

Abstract: The commonality of facial expressions of emotion has been studied in different species since Darwin, with most of the research focusing on closely related primate species. However, it is unclear to what extent there exists common facial expression in species more phylogenetically distant, but sharing a need for common interspecific emotional understanding. Here we used the objective, anatomically-based tools, FACS and DogFACS (Facial Action Coding Systems), to quantify and compare human and domestic dog facial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
95
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(107 citation statements)
references
References 98 publications
9
95
3
Order By: Relevance
“…This too does not match the FACS-coded AUs with potential emotional content of the facial expression. For example, humans focused more on dogs' eyes and mouth in happiness, whereas its core AU appears only on the mouth (Caeiro et al 2017). This is consistent with the finding that similar brain activation occurs when viewing the faces of both species (Blonder et al 2004); i.e., it seems that a human-like facial search strategy is used to perceive dog faces.…”
Section: Human Perception Of Facial Expressionssupporting
confidence: 83%
See 4 more Smart Citations
“…This too does not match the FACS-coded AUs with potential emotional content of the facial expression. For example, humans focused more on dogs' eyes and mouth in happiness, whereas its core AU appears only on the mouth (Caeiro et al 2017). This is consistent with the finding that similar brain activation occurs when viewing the faces of both species (Blonder et al 2004); i.e., it seems that a human-like facial search strategy is used to perceive dog faces.…”
Section: Human Perception Of Facial Expressionssupporting
confidence: 83%
“…Certainly, in relation to emotionally neutral dog faces, humans show a similar gaze distribution to when observing a human face (Guo et al 2010), and this might indicate a wider use of strategies developed for human face assessment in the evaluation of the faces of other species. Although Caeiro et al (2017) found unique relationships between certain AUs and specific emotionally competent triggers, we do not know whether any dog AU combinations are unique to specific emotional states, as occurs in humans; or to what extent humans attend to any of these AUs when dogs are emotionally aroused.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations